1995
DOI: 10.1093/ndt/10.supp6.40
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous versus intravenous administration of erythropoietin improves its efficiency for the treatment of anaemia in haemodialysis patients

Abstract: Recombinant human erythropoietin (rHuEpo) seems to be more efficient when given subcutaneously (SC) instead of intravenously (IV) for therapy of anaemia in haemodialysis patients. This was a cross-over study designed to assess the efficiency of rHuEpo when given SC rather than IV in a 1 year follow-up. Sixteen patients received IV rHuEpo for 6 months, then SC rHuEpo for 6 months. They were four males and 12 females with a mean age of 56 years (range 15-82). Haemoglobin concentration ([Hb]) was kept at 10 g/dl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…25 While intravenous administration results in higher plasma EPO, the subcutaneous route results in longer half-life, longer sustained plasma concentrations, which potentially enable the administration of lower concentrations, and potentially a lower risk of EPO induced hypertension. 26,27 Before proposing the implementation of EPO after ureteral obstruction the most efficient time line, most effective administration route and lowest EPO dose providing beneficial effects must be elucidated. That is the focus of current and future studies at our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…25 While intravenous administration results in higher plasma EPO, the subcutaneous route results in longer half-life, longer sustained plasma concentrations, which potentially enable the administration of lower concentrations, and potentially a lower risk of EPO induced hypertension. 26,27 Before proposing the implementation of EPO after ureteral obstruction the most efficient time line, most effective administration route and lowest EPO dose providing beneficial effects must be elucidated. That is the focus of current and future studies at our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Many, [12][13][14][15][16][17][18][19][20][21] but not all, [22][23][24][25][26][27] previous trials also concluded that the doses of epoetin required to maintain the hematocrit at a given level were lower with a subcutaneous route of administration, but most of those studies were nonrandomized crossover studies in which the patients were switched from the intravenous to the subcutaneous route of administration. This design does not take into consideration the possibility of crossover effects that would, owing to the long half-life of red cells, delay the decrease in hematocrit resulting from an inadequate dose.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from hemodialysis patients suggests that subcutaneous administration is 30%-50% more efficient than the intravenous route. 41,42 Recommendation. Continuing epoetin treatment beyond 6-8 weeks in the absence of response (eg, Ͻ 1-2 g/dL rise in hemoglobin level), assuming appropriate dose increase has been attempted in nonresponders, does not appear to be beneficial.…”
Section: Level Of Evidence (Status Of Evidence): II (Nineteen Comparamentioning
confidence: 99%